Understanding Treatment Resistance in Depression - Karstensen, Valerie; Olsen, Geoffrey; Bastholm, Mathias (KMAN Counseling & Psychology Nexus, 2024)
Treatment-resistant depression (TRD) represents a significant challenge in psychiatric care, affecting a substantial portion of patients who do not respond to conventional treatment modalities. This qualitative study aims to explore the lived experiences of individuals diagnosed with TRD to better understand the personal, social, and systemic factors that contribute to treatment resistance and identify potential avenues for more effective interventions. The study utilized a qualitative design, conducting semi-structured interviews with 33 participants diagnosed with TRD. Data collection continued until theoretical saturation was achieved. Interviews were transcribed and analyzed using NVivo software to facilitate thematic analysis and ensure comprehensive data exploration and theme identification. Four main themes were identified: Personal Experiences with Depression, Interactions with the Healthcare System, Treatment Efficacy and Options, and Psychological and Social Insights. These themes encompassed subthemes such as emotional impact, coping mechanisms, quality of care, medication efficacy, alternative treatments, stigma, and the role of support networks. Each category provided deep insights into the challenges faced by individuals with TRD and the factors influencing their treatment outcomes. The study highlights the complex nature of TRD and underscores the need for a more personalized, empathetic approach in treating this condition. Insights gained suggest that enhancing patient-provider communication, increasing access to alternative treatment options, and addressing societal stigma could improve treatment outcomes for individuals with TRD.